PENANGGULANGAN COVID SEBAGAI SARANA UNTUK MENCIPTAKAN KESEHATAN MASYARAKAT DI LINGKUNGAN DESA JOYOSUKO METRO - Maksum, Ikhsan (JRCE (Journal of Research on Community Engagement), 2021)
The aim of the KKM is to improve the abilities and insights of students as a means of living in society. This year's implementation for our group located in Joyosuko Metro Village is a village in the Malang District, East Java Province. Joyosuko Metro Village is a sub-district center that offers a natural environment and community harmony. This Student Work Lecture (KKM) this year, invites students to research about 5 aspects offered by the campus to the community, including: 1. Education 2. Health 3. Information Technology 4. Religious and 5. Natural Resources or the potential possessed by the community itself, whether from the agricultural, plantation or livestock economy. The main purpose of this activity is to hone the knowledge and experience of students who have gained in the lecture bench, and this activity can help students to go directly to the community. The research method uses a case study with a descriptive qualitative approach. The data collection techniques carried out by researchers are documentation, observation and interviews with participants to obtain valid data. The results of activities in the form of making a village profile and adding to the contents that are considered capable of lifting the village and looked at by the central government. Creating an Penanggulangan covid-19is another excellent program for Joyosuko Metro Village, the aim is to beautify and make the village hall an environmentally friendly office.